The near wake of a sinusoidal wavy cylinder with a large spanwise wavelength using time-resolved particle image velocimetry - Bai, H. L. (2021)
The near wake of a sinusoidal wavy cylinder is investigated using time-resolved particle image velocimetry (TR-PIV). The wavy cylinder has a large spanwise wavelength of six mean diameters. TR-PIV measurements are taken in three orthogonal planes in the near wake at a Reynolds number Re = 3.0 × 10 3 . Flow structures are documented in detail, in terms of time-mean flows, Reynolds stresses, and dominant structures. A substantially long recirculation bubble is observed downstream of the saddle and node planes, corroborating the fact that fluid forces are largely reduced. Furthermore, different frequencies of vortex shedding at the saddle and node are observed for the first time, that is, vortical structures shed from the saddle and node at higher and lower frequencies, respectively. In the cross-stream plane, time-mean streamwise vorticities concentrate between the saddle and node and show an alternating pattern along the spanwise direction. Moreover, results from proper orthogonal decomposition (POD) analyses reveal distinct characteristics in the lower POD modes for the saddle and node planes; meanwhile, upwash/downwash flows downstream of the saddle, together with streamwise vortices, are associated with the lower POD modes in the cross-stream plane. Comparison is made between the present results and that for a wavy cylinder with a relatively small wavelength at similar Reynolds numbers. Graphical abstract: [Figure not available: see fulltext.]